2014
DOI: 10.1109/tnano.2014.2318203
|View full text |Cite
|
Sign up to set email alerts
|

<italic>In-Situ</italic> Silver Nanoparticle Formation on Surface-Modified Polyetherimide Films

Abstract: This paper extends the scope of a novel process previously reported by the group for the hydrolysis and subsequent metallization of polyimide substrates to encompass polyetherimide. Silver nanoparticles are grown in-situ by chemical reduction of silver ions implanted in the substrate. Factors affecting the level of hydrolysis are investigated, with temperature of the hydrolyzing solution found to be the key factor. The presence of silver nanoparticles is also confirmed by X-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The metallisation process was performed as outlined in Figure 1. The PEI surface is first hydrolysed, breaking imide bonds to form amide bonds, which can then receive potassium ions, that are ion exchanged with the desired metal cation (m + ) [3].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The metallisation process was performed as outlined in Figure 1. The PEI surface is first hydrolysed, breaking imide bonds to form amide bonds, which can then receive potassium ions, that are ion exchanged with the desired metal cation (m + ) [3].…”
Section: Methodsmentioning
confidence: 99%
“…reaching a market value of $1.77 Bn, with the growth being driven by thin photovoltaics, wearable electronics and sensing [1]. Polyetherimide (PEI) is a high temperature plastic (Tg=217 o C) offering thermal stability, mechanical strength, high radiation and chemical resistance, good adhesion, and a low dielectric constant [2,3]. For these reasons this material is suited to high value, high temperature applications, but has additional applications in additive manufacturing [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Geng et al [13] reported that the dielectric barrier discharge (DBD) plasma at atmospheric pressure was used to improve the adhesion and hydrophilicity of PET nonwoven fabric. Watson et al [22] reported that the surface modification of PEI via in situ ion exchange in potassium hydroxide (KOH) solution. These methods could introduce functional groups to improve the affinity between the catalyst and surface, and then electroless copper or nickel plating on the surface of polymer.…”
Section: Introductionmentioning
confidence: 99%
“…These methods could introduce functional groups to improve the affinity between the catalyst and surface, and then electroless copper or nickel plating on the surface of polymer. To the best of our knowledge, some expensive reagents are involved and the operation processes are tedious which raise the operation [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%